Multimodality in Audio-Verbo-Visual Translation - Mujiyanto, Yan; Fitriati, Sri Wuli (KnE Social Sciences, 2019)
Until the end of the 20th century, a part of applied linguistics, translation still focuses primarily on verbal rendering. Language elements are explored extensively in translationstudies.Theexplorationsincludeconceptsofequivalence,shift,modulation, and untranslatability. That texts are not only in the form of verbal languages but also audio, visual, gestural, and digital ones has triggered translation studies to explain phenomenaarisingfromtherenderingofintersemiotictexts.Thisstudyaimstoexplain the application of multimodality in the translation of verbo-visual text including the degree of accuracy, naturalness, and acceptability of Indonesian texts translated from English. The object of this study is English Audio-verbo-visual texts and their translationsinIndonesian.Thetypesoftextsinquestionincludevarioustextualgenres commonly existing in dubbing, subtitling, comic and comic rendering. The data for this study were obtained through documentatary studies and were analyzed using the conceptofphenomenology.Theresultsofthisstudyindicatethateachtexttypehasits owncharacteristicssothatintersemiotictranslationcanbedifferentfromonerendering to another. The multimodality of translation may bridge the transfer of meaning in intersemiotic rendering, especially from English to Indonesian. Keywords: intersemiotic translation; multimodality; verbo-visual rendering.